Determinants of Adoption and the Type of Solar PV Technology Adopted in Rural Pakistan - Ahmar, Muhammad; Ali, Fahad; Jiang, Yuexiang; Wang, Yichu; Iqbal, Kashif (Frontiers in Environmental Science, 2022)
The electricity crisis in Pakistan is triggering grid power outage (load shedding) for many decades, which has not only affected the commercial and industrial sectors but also the domestic sector, specifically the livelihood of rural areas of the country. However, the extant literature advocates that renewable energy technologies, such as solar photovoltaic (PV) can be the remedy. Given the abundantly availability of solar energy in Pakistan that can be converted into electrical energy using solar photovoltaic (PV) systems, this study examines the determinants of solar PV adoption in rural areas of Pakistan. Our preliminary investigations – using government/official publications – indicate that despite a huge potential of solar energy in Pakistan, the usage of solar PV at household level in rural areas is still untapped, which makes this research agenda more appealing and provocative. In doing so, this study first conducts surveys, face-to-face comprehensive interviews, and questionnaires in four different districts of Pakistan and then implements a stepwise two-stage novel approach on a sample of 1140 selected rural households. The first stage focuses on the determinants of solar PV adoption, whereas the second stage focuses on the determinants of the type of solar PV adopted. Using logistic regression, this study finds that age, education, children-in-school, income-level, access-to-credit, gender (female), and price of solar-PV system are the factors significantly affecting the solar-PV adoption. In the second stage, we employ multivariate probit model and find that among these significant factors, the former five are significantly positive for the uptake of solar home-system, whereas the latter two are significant for both solar shed-lighting and solar panel-kit systems. In addition to these factors, landholding and access-to-road are significant for solar home-system, whereas household size, distance-to-market, and access-to-grid-electricity are significant for both solar shed-lighting and solar panel-kit systems. Since burning fossil fuel and solid biomass fuels for domestic energy needs are common in rural areas globally that cause carbon emission and several severe health issues, the findings of this study are useful in many ways. In specific, we contribute to the literature examining the determinants of renewable energy technologies in rural communities in developing countries.